SAFETY-LEADERSHIP AND SAFETY CLIMATE EFFECT ON SAFETY OUTCOMES IN OIL & GAS INDUSTRY OF MALAYSIA - MIRZA, MUHAMMAD ZEESHAN (2018)
Occupational safety is the biggest challenge for theorists and practitioners in the 21st century. According to the International Labor Organization, millions of workers suffers workplace accidents and injuries across the world each year. Safety literature affirms that leadership plays a decisive role in ensuring workplace safety.